2018
DOI: 10.1126/science.aau5811
|View full text |Cite
|
Sign up to set email alerts
|

The case for monitoring life-span inequality

Abstract: Inequality in length of life is the most fundamental of all inequalities; every other type of inequality is conditional upon being alive. As has long been recognized in studies of economic inequality, we can compare populations based on per capita gross national income, but there is a pressing need to further examine how income varies within populations via Gini coefficients and percentile-based metrics. Mortality inequalities should be approached in the same way. Human population health is generally monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
186
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(193 citation statements)
references
References 38 publications
4
186
0
3
Order By: Relevance
“…This study has again confirmed that different levels of life disparity can be found in societies with similar levels of life expectancy. 1,25,26 Based on life tables for 212 countries, Smits and Monden argued that countries that achieved a certain level of life expectancy earlier in time were more likely to experience higher levels of inequality. 1 Nevertheless, the study conducted by Seaman and colleagues has shown some opposite findings: Scotland, which caught up with England and Wales in life expectancy, had higher lifespan variations, because of its lower older age mortality yet higher premature adult age mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has again confirmed that different levels of life disparity can be found in societies with similar levels of life expectancy. 1,25,26 Based on life tables for 212 countries, Smits and Monden argued that countries that achieved a certain level of life expectancy earlier in time were more likely to experience higher levels of inequality. 1 Nevertheless, the study conducted by Seaman and colleagues has shown some opposite findings: Scotland, which caught up with England and Wales in life expectancy, had higher lifespan variations, because of its lower older age mortality yet higher premature adult age mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Such reversal is possible if deaths at old ages are further reduced or delayed, while mortality rates at younger age and midlife stall or start to rise. 26 Previous studies have found the stagnation or increase in mortality at younger ages might be related with various socioeconomic factors, contributing to the differences in lifespan variation, particularly among some subpopulations. 27,28 Therefore, policies related to the justification of social arrangements should be in place.…”
Section: Discussionmentioning
confidence: 99%
“…Life span equality matters because it captures a fundamental type of inequality: variation in length of life. This variation is not revealed by life expectancy and other measures of average mortality levels (12). Two populations that share the same level of life expectancy could experience substantial differences in the timing of death, e.g., deaths could be more evenly spread over age in one population than another.…”
mentioning
confidence: 95%
“…Compared to other forms of inequality, age-inequality has been characterized as the most fundamental because it is not conditional upon survivorship and mortality is the ultimate indicator of health (Tuljapurkar 2010;Raalte, Sasson, and Martikainen 2018). The association of socioeconomic status (SES)-or income-and health/mortality has been of great interest for quite a time, and some hypotheses-absolute-/relative-income and income-inequality hypotheses (Wilkinson 1996(Wilkinson , 1997)-have emerged that provided supporting evidence on the positive relationship between the distribution of income and health-although mixed findings have also been reported in different studies (Wilkinson and Pickett 2006), the shape of that association, and the extent to which higher differentials in the income distribution affect the health of the whole population rather than just disadvantaged groups (Preston 1975 Our study builds on previous research that analyzed inequality in the length of life and convergence of mortality across the whole life span, but that emphasized mortality patterns at adult/old ages (Shkolnikov, Andreev, and Begun 2003;Edwards and Tuljapurkar 2005; Engelman, Canudas-Romo, and Agree 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the age distribution of under-5 deaths has been underscored by methodological work (Guillot et al 2012) demonstrating that traditional life table models do not adequately approximate child mortality patterns in SSA, and by the use of age profiles of under-5 mortality to forecast mortality rates (Mejía-Guevara et al 2019) for the assessment of Sustainable Development Goals (SDGs) in SSA. In addition, between-and within-variation in the length of life is an important indicator of health inequality (Edwards and Tuljapurkar 2005;Raalte, Sasson, and Martikainen 2018) and then analyses of the differences in the age pattern of under-5 mortality across and within countries should reflect health disparities at young ages.…”
Section: Introductionmentioning
confidence: 99%